UMKM DI INDONESIA DAN PERSIAPAN MENUJU ASEAN ECONOMIC COMMUNITY 2015 - Nasution, Lokot Zein (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2014)
The establishment of the ASEAN Economic Community (AEC) in December 2015 is to create ASEAN an integrated free trade economy in this region. The goal is to create a region which has a high competitiveness and more equitable economic development. However, the implementation plan of AEC 2015 is criticized for it is like to harm the domestic economy, especially for the smaller economic sectors such as small and medium enterprises (SMEs).The purpose of this study is to assess at the readiness, challenge as well as strategic development of SMEs to face of the AEC 2015. The results of the analysis were based on secondary data processing and critical literature review which showed that SMEs in Indonesia still have high level of risks, particularly in the international markets. The high risks of Indonesian SMEs are due to both internal and external problems. Internal aspect is such as the small SMEs with still low additional production values and inefficiency; while the external aspect is concerned with the policies such as weak infrastructure developments, high transaction costs, and high macroeconomic risks which are not supportive. This condition has positioned SMEs in weak competitiveness in the face of AEC 2015. From that position, then the readiness in the face of the AEC 2015 would also be very weak. It is advisable that the policy making process should be emphasized on the improvement of the internal and external aspects. Improvements internal aspects: (i) strengthening the capital of accessibility; (ii) improving the capacity and quality of production; and (iii) improving the quality of marketing. While the external aspects: (i) improvement of infrastructure; and (ii) improvements in the efficiency of the bureaucracy. Another strategy is necessary if the internal and external aspects of the repair takes a long time (time lag) is to optimize the market potential domestic through the role of government and banking. It is expected that the improvement in both aspects may increase the readiness of SMEs in Indonesia to face of the AEC in 2015.